"Bastaria ao poema apenas a cor da minha pele?": imagens do arquivo literário afro-brasileiro de Paulo Colina - Gustavo de Oliveira Bicalho (2014)
This thesis intends to address the contemporary Afro-Brazilian writers positioning as it may be read through the literary images found in the archive of Paulo Colina, a poet, translator, essayist and fiction author. A reading principle and a place between memory and history, this archive includes texts of various genres in which the ethnic and racial identities are built in tension with the identification as a writer. The opposition between these different identity formations establishes a dilemma which is both literary and intellectual. Interpreted as an issue that concerns the implications of the black identity in the literary writing, this dilemma becomes a central matter in many of Colinas texts. It has been summarized by the author in the final verses of his poem Corpo a corpo (Body-to-body) which lends the title to this thesis: bastaria ao poema apenas/ a cor da minha pele? (would it be sufficient for the poem/ my skin color alone?). Aiming at critically dealing with different manifestations of this question, the thesis adopts methodological contributions brought by the contemporary biographic criticism which integrates facts and fiction through metaphorical correspondences. Through this method, images emerge from the writers archive and rebuild the fragments of an intellectual living. When juxtaposed to the context of appearance of several cultural, political and literary movements which were engaged in the affirmation of black identity in Brazil from the end of the seventies to the beginning of the nineties, these images portrait Colina as a critical, inquisitive and transgressive writer who puts himself in constant shift in between conflicting spaces. So as to study the shifting positions between life and literature, the corpus of this work includes poems, short-stories, essays and translations by the author and also fragments taken from letters, interviews and newspaper pieces. In addition, testimonies by four writers with whom Colina has shared relevant moments of his literary life have been collected for this research. Those writers are: Cuti, Oswaldo de Camargo, Miriam Alves and Abelardo Rodrigues.